Sem lenço, sem documento e com uma Bíblia nas mãos: o movimento estudantil evangélico nos anos sessenta (Without handerchief, without document and a Bible in hands: the evangelical student movement in the sixties). DOI: 10.5752/P.2175-5841.2012v10n26p385 - Quadros, Eduardo Gusmão de (Horizonte, 2012)
The youthful movements has a paper detached in transformations of Brazil’s protestant field during the 50’s and 60’s decades. In this article, we look at the history of evangelical groups inside the universities with religious work: the Academic Christian Association and the University Biblical Alliance of Brazil. To better understand the innovations, we, first, traced a picture of the Brazilian’s Protestantism after World War II. In second place, we make an history of student’s organizations in evangelical tradition, emphasizing its identities, differences and search of presence although ecclesiastical institutions. Finally, we analyze a repressive context inside and outside of protestant churches after military government since April of 1964. We present, thus, different theological proposals, the innovator’s practices and strikes appeared with ecclesiastical institutions in attempt of joint, by young men and women ones, the confessional requirements of churches, the social political paper and the university environment of Sixties.